Factors Influencing Examination Cheating Behaviors by Consumers of Post-Primary Education in Enugu, Nigeria - Ifeoma, Ifediora Raluchukwu; Uzoma, Ifediora Chuka; Christian, Ugwuanyi Chidera (International Journal of Marketing Research Innovation, 2019)
This study evaluates the factors influencing examination cheating behaviors by consumers of post-primary education in Enugu, Nigeria. The study objectives were to; determine whether the gender of consumers of post-primary education has a significant influence on the incidence of examination cheating behaviors in post-primary schools in Enugu, Nigeria, and; ascertain the significant causes of examination cheating behaviors among consumers of post-primary education in Enugu, Nigeria. The study adopted a descriptive research design. Examiners of external and internal examinations in post-primary schools in Enugu, Nigeria were the target population for the study. A sample size of 246 was chosen from this population. A structured questionnaire was the instrument for data collection, while the t-test was used for the hypotheses tests at 5% level of significance. The hypotheses tests revealed that; gender of consumers of post-primary education has no significant influence on the incidence of examination cheating behaviours in post-primary primary schools in Enugu, Nigeria and; inadequate preparation, environmental influence and poor infrastructure in schools are the significant causes of examination cheating behaviors among consumers of post-primary education in Enugu, Nigeria. Following the findings, the study concludes that though male consumers of educational services have a higher tendency of engaging in examination cheating behaviors than female consumers of educational services in Enugu, Nigeria. This influence of gender has been shown to be insignificant. Also, examination cheating behaviors among consumers of educational services in Enugu, Nigeria are caused by a combination of personal attributes of the consumers and group/societal influences.